The inevitable disclosure doctrine: A facade or a curse in the CEO labor market - Fung, Hung-Gay; Li, Tongxia; Lu, Chun; Wen, Min-Ming (Journal of Banking & Finance, 2025)
Our study examines how the adoption of the inevitable disclosure doctrine (IDD) across US state courts affects the relationship between leverage and CEO compensation. We find that the IDD adoption significantly attenuates the typically positive association between leverage and CEO pay. This effect is more pronounced for CEOs with higher ex-ante mobility, greater career concerns, weaker organizational influence, and higher firm-specific skills. Rejecting the IDD, on the other hand, amplifies the positive relationship between leverage and CEO pay. Our findings underscore the influence of labor market dynamics on CEO compensation.